ANALISIS DAMPAK DANA OTONOMI KHUSUS PAPUA DAN PAPUA BARAT TERHADAP IPM - Fahrudin Muhtarulloh (Pusat Kajian Anggaran, 2021)
The Papua Special Autonomy Fund (otsus) has been given to the provinces of Papua for the period 2002-2020 and West Papua for the period 2009-2021. The granting of these funds aims to catch up with development in Papua and West Papua from other regions. The formulation of the problem in this study is how the impact of the Papua and West Papua special autonomy funds on the HDI. While the purpose of this study is to determine the impact of the Papua and West Papua special autonomy funds on the HDI. Based on the results of the study, several conclusions were obtained, namely, first, the special autonomy fund had a positive and significant impact on HDI in Papua and West Papua. Second, the increase in Papua's HDI for the 2002-2010 period by a percentage of 1.11 percent to 1.05 percent in the 2010-2020 period. Meanwhile, West Papua was 1.38 percent to 0.89 percent. Third, the HDI disparity between districts/cities has increased, the Papua HDI disparity for the 2002-2010 period with a percentage of 24.14 percent to 62.07 in the 2010-2020 period. Meanwhile, West Papua was 44.44 percent to 53.85 percent. Efforts that need to be made by the government to increase the benefits of special autonomy are first, the government/DPR RI in revising the Special Autonomy Law for Papua and West Papua must regulate the measurement of the success of otsus. Second, the measurement of the success of special autonomy using the interval category. Third, the government/DPR RI in revising the Special Autonomy Law for Papua and West Papua must regulate the authorized institution to evaluate the implementation of otsus.